Palm oil and its wastes as bioenergy sources: a comprehensive review - Mahlia T.M.I.; Ismail N.; Hossain N.; Silitonga A.S.; Shamsuddin A.H. (Springer Verlag, 2023)
biofuel; palm oil; biomass; electric power plant; Malaysia; waste management; Biofuels; Biomass; Malaysia; Palm Oil; Power Plants; Waste Management